The impact of immigration on the well-being of natives - Alpaslan Akay; Amelie F. Constant; Corrado Giulietti (Institute for the Study of Labor (IZA), 2012)
This paper examines the effect of immigration directly on the overall utility of natives. To the best of our knowledge, this is the first paper to explore such nexus. Combining information from the German Socio-Economic Panel dataset with detailed local labour market characteristics for the period 1997 to 2007, we investigate how changes in the spatial concentration of immigrants affect the subjective well-being of the German-born population. Our results suggest the existence of a robust, positive effect of immigration on natives' well-being. The presence of confounding local labour market characteristics has a negligible impact on the estimates. Furthermore, we find substantial evidence that the effect of immigration on well-being is a function of the assimilation of immigrants in the region. The effect of immigration is higher in regions with an intermediate level of economic assimilation and is essentially zero in areas where immigrants are either least or fully economically integrated. We conduct robustness checks to address the potential endogeneity between subjective well-being and immigration. Our tests indicate that natives are not crowded out by immigrants, and that the sorting of immigrants to regions with higher SWB is weak. This suggests that our main findings are not driven or strongly influenced by reverse causality or selectivity.
Keywords: C90; J61; D63; 330; immigration; subjective well-being; assimilation; Einwanderung; Migranten; Soziale Integration; Bevölkerung; Zufriedenheit; Schätzung; Region; Deutschland